The Application of Compost Extract and Biopesticide in Three Different Varieties of Soybean (Glycine max L.) - Erise Anggraini; Nuni Gofar; Teguh Randi Pradana; Wahyu Tri Patria; Diana Sinurat (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2023)
Soybeans are high in protein and vegetable oil. However, soil fertility, among other factors, has resulted in low production. This study aimed to compare the effects of shrimp shells compost extract (EKKU) and Mushroom Substrate Media Compost Extract (EKMTJ) fertilizers in combination with bio-insecticides with active ingredients from Beauveria bassiana on the growth and production of soybean. This was a factorial randomised design study with two factors.  The first factor was compost extract, with P1: EKKU and P2: EKMTJ. Furthermore, the second factor is a dosage of bioinsecticides with B. bassiana active ingredients of 1 litre/ha (B1) and 2 litres/ha (B2). The results showed that the application of shrimp shell compost extract (EKKU) combined with 2 litres/ha bioinsecticide gave the best results in plant height and shoot weight. On the other hand, the application of mushroom substrate medium compost extract (EKMTJ) gave the best results for wet and dry weight of plant pods and canopy dry weight.